Et si la communication internationale m’était contée ? De quelques échanges sur ses spécificités, ses enjeux, ses théories et ses méthodes - Hamid Mowlana; Christian Agbobli (Communiquer)
This interview with Hamid Mowlana (Professor Emeritus of the American University) aims to present to a French-speaking public some of his ideas and concepts. Hamid Mowlana is a well-known scholar who has contributed to the institutionalization of international communication and its recognition in communication studies. The interview lies upon some critical thoughts on the evolution of research in international communication, the debates and theories that cross the field as well as the methods that are mobilized.